Lightweight alumina sintered compact, member for heat treatment made from the same, and method for manufacturing the same
The development of a lightweight alumina sintered body with a tailored composition and structure addresses the inefficiencies of existing heat treatment components by providing enhanced heat shock resistance, durability, corrosion resistance, and reduced heat capacity for improved energy efficiency.
Patent Information
- Application Number
- JP2023169770
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Existing heat treatment components lack excellent heat shock resistance, durability, corrosion resistance, and have high heat capacity, making them inefficient for rapid temperature control and energy-saving applications.
A lightweight alumina sintered body with a specific composition and structure, including a corundum and mullite phase content, porosity, and particle size distribution, is developed to enhance thermal shock resistance, durability, and corrosion resistance while reducing heat capacity.
The lightweight alumina sintered body achieves excellent heat shock resistance, durability, and corrosion resistance, along with a low heat capacity, making it suitable for efficient heat treatment processes and energy-saving applications.
Smart Images

Figure 2025059593000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a lightweight alumina sintered body, a heat treatment member made of the lightweight alumina sintered body, and a method for producing the lightweight alumina sintered body. [Background technology]
[0002] Advanced materials, including electronic materials, are becoming smaller and more sophisticated year by year, and as a result, precise composition control of materials is essential. In the heat treatment process, which is one of the manufacturing processes, there are cases where the target characteristics cannot be obtained if composition changes occur due to component evaporation caused by heating, so rapid heating and cooling is performed. However, when heat treatment components with large heat capacity are used, there is a temperature difference between the temperature inside the furnace and the sintered object, which results in disadvantages such as the need for time to bring the sintered object to the specified temperature and the need for cooling, which makes it impossible to achieve the target rapid heating and cooling and increases the amount of energy required for heating. Traditionally, dense heat treatment components have been used because of their excellent corrosion resistance and durability, but because they have low thermal shock resistance, they cannot withstand rapid heating and cooling, and they explode and crack in the furnace, scattering the treated object, causing contamination inside the furnace, as well as the problem of requiring a long time to recover if used continuously. On the other hand, refractory heat treatment components have the disadvantages of being poor in corrosion resistance and durability, although they have excellent thermal shock resistance. In particular, repeated use can cause the particles that make up the refractory to fall off and become mixed into the product being fired, or can cause fine cracks to develop, which can grow with repeated use and lead to fracture.
[0003] As described above, the heat treatment process of advanced materials requires a heat treatment member that is excellent in thermal shock resistance, durability, and corrosion resistance and enables highly efficient heat treatment. For example, Patent Document 1 discloses a sintering tool material made by mixing electrofused alumina and mullite of a specified particle size with low soda calcined alumina in a specific blending amount, but since the dispersion state of the mixed powder is not taken into consideration, the structure has low uniform dispersion of large and small particles, and is inferior in thermal shock resistance and durability. In addition, Patent Document 2 discloses a lightweight refractory material that uses hollow alumina raw material, controls the particle size distribution of the raw material powder, and has high strength and excellent spalling resistance. However, since the alumina content is low, the corrosion resistance is low and it cannot be used for the heat treatment of advanced materials that require precise composition control. Although the porosity is 20% or more, it is lightweight, but if the porosity is about 20%, it is a porosity that is also possessed by ordinary refractories, and it cannot be said to be lightweight, and it is clear that it does not have a low heat capacity, and it is considered to have no effect on energy saving. Furthermore, Patent Document 3 discloses an alumina refractory produced by mixing fine alumina raw material powder and coarse alumina raw material powder in a specific blending ratio, and the porosity of the resulting refractory is set to 20 to 40%, and the pore diameter is set to 10 μm or less. However, the refractory is inferior not only in thermal shock resistance but also in durability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-252677 A [Patent Document 2] Japanese Patent Application Publication No. 11-189480 [Patent Document 3] JP 2011-88759 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide an alumina sintered body and a member for heat treatment that are excellent in thermal shock resistance, durability, and corrosion resistance, and also to provide a member for heat treatment that has low heat capacity in addition to these properties. [Means for solving the problem]
[0006] The present inventors have conducted intensive research to obtain an alumina-based heat treatment member having excellent thermal shock resistance, durability, and corrosion resistance, which can replace conventional refractories and dense heat treatment members made of advanced materials such as electronic materials. As a result, it has been found that by controlling the content of mullite crystals, the content of alumina, the porosity, the average pore size, and the dispersion state of coarse alumina crystal particles in an alumina-based sintered body and setting them within a specific range, it is possible to improve not only the corrosion resistance of the alumina-based sintered body, but also the thermal shock resistance and durability, and furthermore, it is possible to suppress the deterioration of mechanical properties such as strength that usually occurs when the porosity is increased. The alumina-based sintered body in which these items are controlled and set within a specific range largely solves the problems of conventional refractories and dense heat treatment members, and is excellent as a heat treatment member. Furthermore, this alumina-based sintered body has the characteristics of being lightweight and having a low heat capacity, and therefore has the advantage of being able to save energy in the heat treatment process. The inventors have also found that such a lightweight alumina sintered body can be manufactured by using as a raw material a mixture of two kinds of alumina powders, coarse and fine, which have high purity and different specific average particle sizes, and mullite powder, which has a certain alumina to silica ratio and a specific average particle size, in a specific ratio. Here, the specific ratio when mixed is the ratio between the two kinds of alumina powders and the ratio between the coarse alumina powder and the mullite powder, and a manufacturing method in which these ratios are controlled has not been known until now. The lightweight alumina sintered body newly discovered by the inventors not only has excellent mechanical properties such as thermal shock resistance, durability, and corrosion resistance, but also has an excellent property of low heat capacity, and can be suitably used as a container used in the heat treatment of various materials to be heat treated, and a member used in various firing furnaces, etc. The present invention has been completed in this way.
[0007] That is, the present invention is specified by the following items. (1) A lightweight alumina sintered body that satisfies the following requirements (a) to (e): (a) The crystal phase is composed of two phases, a corundum phase and a mullite phase, and the content of the mullite phase is 15 to 30%. (b) The alumina content is 90 to 94 mass %. (c) The porosity is 30 to 50%. (d) The average pore size is 20 μm or less. (e) Area 25mm 2 The number of crystal grains having a size of 500 μm or more present in the powder is 10 to 15, and the coefficient of variation in the number of crystal grains is 0.2 or less. (2) A heat treatment member comprising the lightweight alumina sintered body described above in (1). (3) A method for producing a lightweight alumina sintered body according to (1), comprising mixing a coarse alumina powder having an alumina content of 99.7% by mass or more and an average particle size of 500 to 1400 μm with a fine alumina powder having an alumina content of 99.7% by mass or more and an average particle size of 5 to 20 μm so that the mass ratio of the coarse alumina powder to the fine alumina powder (coarse alumina powder / fine alumina powder) is 0.55 to 0.85, mixing and dispersing mullite powder having an alumina to silica mass ratio of Al2O3 / SiO2 of 74 / 26 to 78 / 22 and an average particle size of 700 to 2000 μm into the mixture so that the mass ratio of the mullite powder to the coarse alumina powder (mullite powder / coarse alumina powder) is 0.85 to 1.30, molding the mixture, and then sintering the mixture at 1500 to 1700° C. Effect of the Invention
[0008] The lightweight alumina sintered body of the present invention and a member for heat treatment made from the same are excellent in thermal shock resistance, durability, and corrosion resistance. In addition, the lightweight alumina sintered body of the present invention and a member for heat treatment made from the same have a low heat capacity. Due to these characteristics, the lightweight alumina sintered body of the present invention and a member for heat treatment made from the same are excellent as members used for heat treatment applications. The manufacturing method of the present invention can manufacture the lightweight alumina sintered body of the present invention. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a view showing a microscope image of the sintered body obtained in Example 9. [Diagram 2] FIG. 2 is a view showing a microscope image of the sintered body obtained in Comparative Example 3. [Diagram 3] FIG. 3 is a diagram showing the X-ray diffraction pattern of the sintered body obtained in Example 9. [Figure 4] FIG. 4 is a diagram showing the X-ray diffraction pattern of the sintered body obtained in Comparative Example 5. [Diagram 5] FIG. 5 is a diagram showing the X-ray diffraction pattern of the sintered body obtained in Comparative Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The lightweight alumina sintered body of the present invention satisfies all of the following requirements (a) to (e): (a) it is composed of two crystalline phases, a corundum phase and a mullite phase, with the mullite phase content being 15 to 30%, (b) it has an alumina content of 90 to 94 mass%, (c) it has a porosity of 30 to 50%, (d) it has an average pore diameter of 20 μm or less, and (e) it has an area of 25 mm 2 The number of crystal grains of 500 μm or more present in the sintered body is 10 to 15, and the coefficient of variation of the number of crystal grains is 0.2 or less. The term "lightweight" in the lightweight alumina sintered body of the present invention means that the bulk density is low, that is, the porosity is large. In the present invention, the heat treatment member is a member used in heat treatment, and is a member used in general heat treatment such as a container, a stand, or various firing furnaces for containing or placing an object to be heat treated. Examples of the heat treatment member of the present invention include members used in the manufacture of containers, setters, tubes, etc. used in the synthesis and firing of electronic materials and secondary battery materials, the firing of various ceramic products, metal melting, and single crystal growth. The following requirements (a) to (e) of the present invention will be described in detail.
[0011] (a) It consists of two crystalline phases, corundum and mullite, with the mullite content being 15 to 30%. The crystal phase in the present invention must be two phases, a corundum phase and a mullite phase. The corundum phase alone not only has low thermal shock resistance, but also has the risk of cracking due to repeated heating and cooling, which leads to strength deterioration and reduced durability. By containing the mullite phase, it is possible to have high thermal shock resistance and durability, but if the mullite phase content is less than 15%, the effect of containing the mullite phase is reduced. On the other hand, if it exceeds 30%, the distortion due to the thermal expansion difference between the mullite phase and the corundum phase becomes large, which leads to not only a decrease in strength but also a decrease in thermal shock resistance and durability. Furthermore, since the amount of silica contained increases due to the increase in the mullite phase, the corrosion resistance, especially against alkaline components, is reduced. From the viewpoint of further improving thermal shock resistance and durability, the content of the mullite phase in the present invention is preferably 20 to 30%, more preferably 22 to 28%.
[0012] In the present invention, the qualitative and quantitative analysis of the crystal phase is carried out by pulverizing the sintered body to an average particle size of 5 μm or less and using a powder X-ray diffractometer. The content ratio of the mullite phase is determined by the diffraction intensity of the (113) crystal face of the corundum phase (A): A Diffraction intensities of (113) and (210) crystal faces of mullite phase (M): I M The alumina sintered body of the present invention has no clear crystal peaks indicating crystal phases other than the corundum phase (A) and mullite phase (M) when measured by X-ray diffraction, and the shape of the X-ray diffraction pattern indicates good crystallinity.
[0013]
number
[0014] (b) The alumina content is 90 to 94 mass %. In the present invention, the alumina content in the lightweight alumina sintered body is 90-94 mass%, preferably 91-93 mass%, from the viewpoint of corrosion resistance. If the alumina content is less than 90 mass%, the sintered body will contain a large amount of impurities, resulting in a decrease in corrosion resistance. On the other hand, if the alumina content exceeds 94 mass%, the mullite phase will decrease, and the effect of containing the mullite phase will decrease. Note that the impurities in the present invention are CaO, MgO, Na2O, K2O, ZrO2, etc., and the content of the impurities is preferably 1.0 mass% or less, more preferably 0.7 mass% or less. If the content of the impurities exceeds 1.0 mass%, the corrosion resistance may decrease.
[0015] (c) Porosity is 30-50%. In the present invention, since it is necessary to reduce the weight in order to reduce the heat capacity, the porosity of the lightweight alumina sintered body must be 30-50%, preferably 32-48%, and more preferably 35-47%. If the porosity is less than 30%, the strength will increase, but the repeated heating and cooling will cause large expansion and contraction, which will lead to deterioration, and the sintered body will have a high density, resulting in a high heat capacity. On the other hand, if the porosity exceeds 50%, the porosity will be too high, which is effective in reducing the weight, but will result in a decrease in mechanical properties. Generally, an increase in porosity will cause a decrease in mechanical properties and corrosion resistance, but the lightweight alumina sintered body of the present invention has a microstructure that enhances the dispersion of large crystal particles, making it possible to suppress the decrease in properties caused by increasing the porosity to 30-50%. The porosity in the present invention refers to the apparent porosity, and can be measured by the Archimedes method (in accordance with JIS R2205).
[0016] (d) The average pore diameter is 20 μm or less. In the present invention, the average pore size of the lightweight alumina sintered body is 20 μm or less, preferably 15 μm or less. The lightweight alumina sintered body of the present invention is different from the alumina sintered body that has been used as a refractory material in the past, in that the ratio of large crystal grains to small crystal grains is controlled and uniformly dispersed, thereby making the pore size small despite the large porosity. If the average pore size exceeds 20 μm, not only will mechanical properties such as thermal shock resistance (thermal shock resistance) and corrosion resistance decrease, but the crystal grains will easily fall off during use, and especially when used as a heat treatment member, there is a risk that the particles that fall off during heat treatment will be mixed into the powder to be treated as impurities. In addition, if the average pore size exceeds 20 μm, in addition to the large heat capacity, when used as a container for heat treatment of raw material powder, the raw material powder will be caught in the open pores, which not only reduces the handleability but also makes it easy to react with the heat treatment material, which is not preferable. The average pore size was measured by mercury intrusion porosimetry and calculated using the following formula (2): In formula (2), P is pressure (MPa) and γ is the surface tension of mercury (480 dyne cm). -1 , θ represents the contact angle of mercury, which is 140°.
[0017]
number
[0018] (e) Area 25mm 2 The number of crystal grains having a size of 500 μm or more present in the powder is 10 to 15, and the coefficient of variation of the number of crystal grains is 0.2 or less. In the present invention, the area is 25 mm 2 The number of crystal grains having a size of 500 μm or more is 10 to 15, and the coefficient of variation of the number of crystal grains is 0.2 or less. 2The number of crystal grains of 500 μm or more present in the sintered body is preferably 11 to 14, and the coefficient of variation is preferably 0.15 or less. The sintered body of the present invention has a higher porosity than conventional sintered bodies, and therefore there is a risk of a decrease in mechanical properties. However, by dispersing crystal grains of 500 μm or more as uniformly as possible, it is possible to suppress the decrease in mechanical properties due to the high porosity. In the present invention, 2 The dispersibility of crystal particles of 500 μm or more is evaluated by determining the number of crystal particles of 500 μm or more present in the sample and the coefficient of variation. The measurement method involves embedding a sintered sample in resin, grinding it flat using a surface grinder or similar, polishing it with diamond abrasive grains to a mirror finish, and observing the structure. Digital microscopes, scanning electron microscopes, metallurgical microscopes, etc. can be used for observing the structure. From the structure observation, a 5 mm long x 5 mm wide (area 25 mm 2 ) square is obtained, the image is analyzed, the area of each crystal grain is calculated, and the area is converted into a circle. Then, crystal grains with a diameter of 500 μm or more when converted into a circle are located within a 25 mm 2 The number of crystal particles present in an area of 5 mm is determined. The number of crystal particles present on the boundary line of a section of 5 mm length x 5 mm width is considered to be 1 / 2. The above measurement is carried out on at least 5 images by changing the observation position, and the number of crystal particles with a diameter of 500 μm or more in each image is determined. The average number of crystal particles in the measured images (i.e., the total number of crystal particles with a diameter of 500 μm or more divided by the number of images) is then calculated as the average value of the number of crystal particles in the measured images (i.e., the total number of crystal particles with a diameter of 500 μm or more divided by the number of images) for an area of 25 mm in the present invention. 2 The number of crystal grains of 500 μm or more present in the sample is defined as the number of crystal grains of 25 mm2 or more present in the sample. 2 The standard deviation of the number of crystal grains having a size of 500 μm or more present in the sample is calculated, and the value calculated from the calculated standard deviation and the average value of the number of crystal grains using the following formula (3) is defined as the coefficient of variation in the present invention. 2 The number of crystal grains having a diameter of 500 μm or more present in the glass includes both corundum crystal grains and mullite crystal grains, so long as the diameter of the crystal grains obtained above is 500 μm or more.
[0019]
number
[0020] If the number of crystal grains of 500 μm or more is less than 10, the number of coarse alumina grains as aggregates is small, which leads to a decrease in thermal shock resistance and durability. If the number exceeds 15, the number of crystal grains less than 500 μm present between crystal grains of 500 μm or more is small, which reduces the bonding strength of the crystal grains, resulting in a decrease in mechanical properties. If the coefficient of variation exceeds 0.2, this means that the dispersion of crystal grains of 500 μm or more is low, and the uniformity of crystal grains of 500 μm or more in the entire sintered body is low, which leads to a decrease in mechanical properties. In addition, the lightweight alumina sintered body of the present invention preferably has a surface roughness Ra of 15 to 30 μm.
[0021] The method for producing the lightweight alumina sintered body of the present invention is described below. The method for producing the lightweight alumina sintered body of the present invention is not particularly limited, but the lightweight alumina sintered body of the present invention is a lightweight alumina sintered body that satisfies the above requirements (a) to (e), and such a lightweight alumina sintered body of the present invention can be produced by the following method. A coarse alumina powder having an alumina content of 99.7 mass% or more and an average particle size of 500 to 1400 μm is mixed with a fine alumina powder having an alumina content of 99.7 mass% or more and an average particle size of 5 to 20 μm. The coarse alumina powder in the manufacturing method of the present invention is not particularly limited as long as it is an alumina powder having an alumina content of 99.7% by mass or more and an average particle size of 500 to 1400 μm, and the fine alumina powder is not particularly limited as long as it is an alumina powder having an alumina content of 99.7% by mass or more and an average particle size of 5 to 20 μm, and examples thereof include pulverized fused alumina and pulverized alumina (low soda alumina) produced by the Bayer process. In addition, bubble alumina powder can be used as the coarse alumina powder. The bubble alumina powder is an alumina powder having a spherical and hollow structure, and the bubble alumina powder preferably has an average particle size of 500 to 1000 μm, and is preferably used in an amount of 5 to 15% by mass of the entire coarse alumina powder. Since the bubble alumina powder is spherical, it has a high bond with the fine alumina powder, and has the effect of increasing resistance to crack development occurring inside the sintered body due to stress load.
[0022] A mixture of coarse alumina powder and fine alumina powder is mixed with mullite powder having an average particle size of 700 to 2000 μm and an alumina to silica mass ratio of Al2O3 / SiO2 of 74 / 26 to 78 / 22. A predetermined amount of paraffin particles, polyethylene resin particles, acrylic resin particles, polysaccharide particles, cellulose, etc. are mixed into the thus obtained mixed powder of alumina and mullite as a pore forming agent to obtain a predetermined porosity, and a predetermined amount of water, surfactant (polycarboxylate, etc.) and binder (PVA, methyl cellulose, wax emulsion, etc.) are added to the mixture using a ball mill, mixer, high-speed stirrer, etc. to prepare a mixed powder slurry. In order to improve moldability and sinterability, clay such as woodbush clay, frog's eye clay, and kaolin may be added in an amount of 3 to 8 mass% to the mixed powder. A molded body is produced using the obtained slurry. When press molding is used as a molding method, the slurry is dried and sized to form a powder. When casting molding is used, the slurry is poured into a plaster mold or a resin mold to form the powder. When extrusion molding is used, the slurry is dried, a predetermined amount of binder (methyl cellulose, cellulose, etc.) is added and mixed, kneaded, and extrusion molding is performed. The obtained molded body is dried and then fired to obtain the lightweight alumina sintered body of the present invention, which is suitable for heat treatment members. The firing temperature is preferably 1500 to 1700°C, and more preferably 1550 to 1650°C. The lightweight alumina sintered body of the present invention produced by the production method of the present invention has a surface roughness Ra of 15 to 30 μm. Even when the lightweight alumina sintered body is used as a heat treatment member to produce a heat treatment container and the powder is used as the heat treatment object, there is almost no adhesion of the powder to the surface of the lightweight alumina sintered body, i.e., the inner surface of the container, and in this respect, the lightweight alumina sintered body is also suitable for heat treatment members.
[0023] In the above-mentioned manufacturing method, the mixing ratio of the coarse alumina powder having an alumina content of 99.7% by mass or more and an average particle diameter of 500 to 1400 μm to the fine alumina powder having an alumina content of 99.7% by mass or more and an average particle diameter of 5 to 20 μm is preferably such that the mass ratio of the coarse alumina powder to the fine alumina powder (coarse alumina powder / fine alumina powder) is 0.55 to 0.85, more preferably 0.58 to 0.80. The mixture of the coarse alumina powder and the fine alumina powder is mixed with the mullite powder having an average particle size of 700 to 2000 μm and an alumina to silica mass ratio of Al2O3 / SiO2 of 74 / 26 to 78 / 22, so that the mass ratio of the mullite powder to the coarse alumina powder (mullite powder / coarse alumina powder) is preferably 0.85 to 1.30, more preferably 0.90 to 1.15. If the coarse alumina powder / fine alumina powder ratio is less than 0.55, the amount of the coarse alumina raw material powder as aggregate in the sintered body is reduced, resulting in a decrease in mechanical properties such as thermal shock resistance and durability. On the other hand, when the ratio of the coarse alumina powder to the fine alumina powder exceeds 0.85, the amount of the coarse alumina powder is large and the amount of the fine alumina powder is small, so that the sinterability is reduced, and the bonding strength between the crystal particles is reduced, resulting in a reduction in thermal shock resistance and durability. Furthermore, the surface roughness of the sintered body is also rougher than that of the sintered body of the present invention, so that the coarse particles are more likely to fall off during use, and when used as a container for heat treatment of raw material powder, the fallen particles may be mixed as impurities into the treated raw material powder. When the ratio of the mullite powder to the coarse alumina powder is below 0.85, the amount of the mullite crystal phase contained in the sintered body is reduced, leading to a reduction in the effect of the mullite crystal phase on thermal shock resistance and durability. On the other hand, when the ratio of the mullite powder to the coarse alumina powder exceeds 1.30, the amount of the mullite phase contained in the sintered body is increased, and the difference in thermal expansion between the mullite phase and the corundum phase causes distortion in the sintered body due to repeated heating and cooling, leading to a reduction in mechanical properties such as thermal shock resistance and durability.
[0024] In the present invention, since it is important to uniformly disperse each powder having a different particle size, it is necessary to add a surfactant appropriately when mixing each powder, and mix and disperse the powder by lowering the viscosity of the slurry as much as possible. The surfactant is not particularly limited, and a commonly used surfactant can be used, but examples thereof include nonionic surfactants, anionic surfactants, and cationic surfactants, and examples thereof include polycarboxylates, sulfate ester salts, and sulfonates. The amount of the surfactant to be added can be appropriately selected and is not particularly limited, but examples thereof include 0.1 to 2 mass% relative to the total amount of the raw material powder. In addition, when the obtained slurry is dried or cast-molded, the slurry is in a state in which the particles are dispersed with low viscosity due to the addition of a surfactant, so that the coarse particles and fine particles do not separate during drying or molding, by appropriately adding and mixing a thickener, the separation of the coarse particles and fine particles and the sedimentation of the coarse particles can be suppressed, and the dispersibility of the raw material powder particles can be increased. The thickener is not particularly limited, and any commonly used thickener can be used, for example, polyacrylic thickeners, urethane thickeners, etc., such as acrylic resins, polyethers, polycarboxylic acids, etc. The amount of thickener to be added can be appropriately selected without any particular limitation, and for example, it can be 0.1 to 5 mass % based on the total amount of the raw material powder.
[0025] The heat treatment member of the present invention is a heat treatment member made of the lightweight alumina sintered body of the present invention, and can be produced from the lightweight alumina sintered body of the present invention. The shape is not particularly limited, and can be a container-like, table-like, plate-like, rod-like, etc., and can be produced by forming the lightweight alumina sintered body of the present invention into a desired shape when forming it, or by cutting the lightweight alumina sintered body of the present invention into a predetermined shape, polishing, etc. Also, it can be produced by bonding, joining, etc. the lightweight alumina sintered body of the present invention. The heat treatment member of the present invention has excellent thermal shock resistance, durability, and corrosion resistance, and has a low heat capacity, so it can be suitably used as a heat treatment member used for heat treatment applications. EXAMPLES
[0026] The present invention will be specifically described below by way of examples of the present invention, but the technical scope of the present invention is not limited to these examples.
[0027] [Examples 1 to 11 and Comparative Examples 1 to 11] In Examples 1 to 11 and Comparative Examples 1 to 11, a fused alumina powder having an average particle diameter of 1000 μm was used as the coarse alumina powder, and a low soda alumina powder having an average particle diameter of 16 μm was used as the fine alumina powder. In Example 9 and Comparative Example 7, 12% of the coarse alumina powder was not fused alumina powder but bubble alumina powder having an average particle diameter of 1000 μm. As the mullite powder, a fused mullite powder having an Al2O3 / SiO2 (mass ratio) of 76 / 24 and an average particle diameter of 1400 μm was used. In addition, in order to control the porosity, a pore former was used in all cases except Comparative Example 4. As the pore-forming agent, in Examples 1 and 10 and Comparative Examples 6 and 8, corn starch with an average particle diameter of 17 μm was used, in Examples 2 to 9 and 11 and Comparative Examples 2, 3, 5, 7, and 9 to 11, acrylic resin particles with an average particle diameter of 15 μm were used, and in Comparative Example 1, acrylic resin particles with an average particle diameter of 35 μm were used. First, coarse alumina powder and fine alumina powder were mixed, and mullite powder was mixed into the resulting mixture. Kaolin powder was added to the resulting mixture of alumina powder and mullite powder in an amount of 5 mass% relative to the total amount of the mixture of alumina powder and mullite powder in order to improve moldability and sinterability. Next, a pore-forming agent was added so as to obtain a predetermined porosity. The coarse alumina powder, fine alumina powder, mullite powder, kaolin powder, and pore-forming agent were mixed in a wet manner using water, with an appropriate amount of polycarboxylate ammonium salt (surfactant) added, using a high-speed mixer to prepare a mixed slurry. An acrylic resin was appropriately added as a thickener to the obtained mixed slurry to thicken it to a degree that would not cause separation or sedimentation of the powder particles, to obtain a molding slurry. In Comparative Example 2, no thickener was used, and in Comparative Example 6, no surfactant was used. Table 1 shows the coarse alumina powder / fine alumina powder (mass ratio), mullite powder / coarse alumina powder (mass ratio), alumina content (mass%), silica content (mass%), and impurity content (mass%) in Examples 1 to 11 and Comparative Examples 1 to 11.
[0028] (Area 25mm 2 (Measurement of the number of crystal grains of 500 μm or more present in the sample and the coefficient of variation) The slurries obtained in Examples 1 to 11 and Comparative Examples 1 to 11 were molded using a vibration molding machine, dried, and then fired at the temperatures shown in Table 1. H A sintered body was prepared in a container of 30 mm in diameter, and cut out from the bottom of the container to a size of 30 x 30 x 5 mm. The cut out body was embedded in resin and ground to a flat surface using a surface grinding machine or the like. It was then polished with diamond abrasive grains to a mirror finish, and an image was taken at a magnification of 30 times using a Keyence digital microscope VHX-6000. From the image obtained, a 5 mm long x 5 mm wide (area 25 mm 2 The area of the crystal grains was calculated by cutting out the image of the area of each crystal grain, and analyzing the image using IMAGEJ (free software). The area of the crystal grains was calculated by converting the calculated area into a circle, etc., and the diameter of the crystal grains was calculated as 25 mm2. 2 This measurement was performed on five images cut out from different positions, and the number of crystal grains with a diameter of 500 μm or more obtained from the five images was calculated based on the average value and standard deviation of the number of crystal grains with a diameter of 500 μm or more in the area of 25 mm 2 The number of crystal grains of 500 μm or more present in the sample and the coefficient of variation in the number of crystal grains were determined. The number of crystal grains of 500 μm or more and the coefficient of variation are shown in Table 1. Figures 1 and 2 show images cut out to a size of 5 mm length x 5 mm width. Figure 1 is one of the five images of the sintered body of Example 9 observed above, and Figure 2 is one of the five images of the sintered body of Comparative Example 3 observed above. In Figure 1, a 25 mm 2 In the area of 25 mm, there are 11 crystal grains with a diameter of 500 μm or more. 2 The number of crystal grains with diameters of 500 μm or more in the area was 6.5.
[0029] (Porosity and average pore size measurements) Test pieces were cut out from the sintered bodies obtained in Examples 1 to 11 and Comparative Examples 1 to 11, and the porosity and average pore size were measured. The porosity was measured by the Archimedes method using a 20×20×10 mm test piece, and the pore size was measured by the mercury intrusion method using a porosimeter using a 10×10×10 mm test piece.
[0030] (Measurement of Mullite Phase Content) The sintered bodies obtained in Examples 1 to 11 and Comparative Examples 1 to 11 were pulverized to an average particle size of 5 μm or less, and measurements were performed using a powder X-ray diffractometer (D8 ADVANCE manufactured by Bruker Japan) with Cu as the target under the following conditions: step of 0.02°, step time of 0.4°, voltage of 40 kV, current of 40 mA, entrance side divergence slit of 0.5°, entrance side Soller slit of 4.1°, receiving side divergence slit of 5.2°, and receiving side Soller slit open. The content ratio of the mullite phase was determined by the diffraction intensity of the (113) crystal face of the corundum phase (A): I A Diffraction intensities of (113) and (210) crystal faces of mullite phase (M): I M From (210), the content ratio of mullite phase (%) = [I M (210) / (I A (113)+I M The diffraction coefficient was calculated by the following formula: (210) × 100. As a result of the X-ray diffraction measurement, in Examples 1 to 11, no crystal phase other than the corundum phase (A) and the mullite phase (M) was observed, and the X-ray diffraction patterns showed clear peaks, so that it was found that the obtained sintered bodies were composed almost entirely of the corundum phase (A) and the mullite phase (M). The X-ray diffraction pattern of the sintered body obtained in Example 9 is shown in FIG. 3, the X-ray diffraction pattern of the sintered body obtained in Comparative Example 5 is shown in FIG. 4, and the X-ray diffraction pattern of the sintered body obtained in Comparative Example 11 is shown in FIG. 5.
[0031] (Thermal shock resistance test and durability test) The sintered bodies obtained in Examples 1 to 11 and Comparative Examples 1 to 11 were cut out and processed with a diamond grindstone of #140 mesh to prepare test pieces of 6 x 8 x 70 mm, which were then placed in an electric furnace at 700 ° C., held for 30 minutes, and then dropped into water at 10 ° C. to conduct a thermal shock resistance test. The test pieces after the test were evaluated by visually checking whether or not cracks had occurred. In addition, the durability test was performed using the same test pieces as the samples used in the thermal shock resistance test, and was repeated 20 times at a predetermined temperature under the same conditions as the thermal shock resistance test, and the presence or absence of cracks was evaluated by visual inspection. The results are shown in Table 1. In Table 1, the cases where no cracks were generated by the thermal shock resistance test are indicated by a circle, and the cases where cracks were generated are indicated by a cross. In addition, the results of the durability test in Table 1 indicate the number of tests when cracks were observed, and >20 indicates that no cracks were observed even after 20 repetitions.
[0032] (Bending strength test) The 8×70 mm surface of the 6×8×70 mm test pieces of Examples 1 to 11 and Comparative Examples 1 to 11, which were processed in the same manner as in (Thermal Shock Resistance Test and Durability Test), was used as the tensile surface, and measurements were performed on five samples for each specimen using a precision universal testing machine (AGS-500NX, manufactured by Shimadzu Corporation) under conditions of four-point bending with an upper span of 10 mm, a lower span of 30 mm, and a crosshead speed of 0.5 mm / min, and the average value was calculated. The results are shown in Table 1.
[0033] [Table 1]
[0034] (Heat capacity test) The heat capacity was evaluated using the sintered body obtained in Example 9 and the sintered body obtained in Comparative Example 4. HA sintered compact container of 1.5 mm was filled with 500 g of electrically fused zirconia having an average particle size of 800 μm, a thermocouple was inserted into the electrically fused zirconia powder, the container was closed with a lid and placed in an electric furnace in a sealed state, and the temperature was increased to 1350° C. at a heating rate of 5° C. / min and the time until the temperature inside the container reached 1350° C. was measured. The sintered compact of Example 9, which satisfies all the requirements of the present invention, was heated to the same temperature as inside the electric furnace in 45 minutes, but the sintered compact of Comparative Example 4, which does not satisfy the requirements of the present invention, was heated only to 1340° C. even after 60 minutes. It was clear that the heat treatment member of the present invention has high temperature tracking ability.
[0035] The sintered bodies obtained in Examples 1 to 11 were excellent in thermal shock resistance, with no cracks occurring in the thermal shock resistance test. Furthermore, in the durability test, no cracks occurred even after 20 repeated thermal shocks, demonstrating excellent durability. In addition, despite the high porosity of 30 to 50%, bending strength of 5.0 MPa or more was obtained, demonstrating excellent thermal shock resistance, durability, and mechanical strength.
[0036] In Comparative Examples 1, 4, 7, and 10, no cracks were generated in the thermal shock resistance test with one thermal shock, but because some of the requirements of the present invention were not satisfied, the durability test showed that the thermal shock could not be repeated up to 20 times, and cracks were generated after fewer times than this. In Comparative Examples 2, 3, 5, 6, 8, 9, and 11, cracks were generated in the thermal shock resistance test with one thermal shock. From these results, it was found that lightweight alumina sintered bodies excellent in thermal shock resistance and durability can be obtained by satisfying all of the requirements of the present invention, and these can be suitably used for applications as heat treatment members.
[0037] In Comparative Example 1, a pore-forming agent with an average particle size of 35 μm was used, so that the average pore size of the sintered body was larger than 20 μm, and the durability was reduced. In Comparative Example 2, molding was performed without adding a thickener to the mixed slurry, so that the raw material powder particles settled, and as a result, the dispersibility of the coarse powder particles in the sintered body was reduced, the variation in the number of particles per unit area was increased, and the coefficient of variation in the number of crystal particles of 500 μm or more was larger than 0.2, and the thermal shock resistance and durability of the sintered body were reduced. In Comparative Example 3, the coarse alumina powder / fine alumina powder (mass ratio) was smaller than 0.55, so that the amount of coarse alumina powder as aggregate in the sintered body was reduced, and the number of crystal particles of 500 μm or more was smaller than 10, and the thermal shock resistance and durability were low. In Comparative Example 4, the sintered body was produced without adding a pore-forming agent, so the porosity was less than 30%, and the durability was poor. Also, the heat capacity was higher than that of the sintered body of the present invention, so the temperature follow-up ability in the furnace was low. In Comparative Example 5, the alumina content was higher than 94 mass%, so the mullite phase content was reduced, and the mullite phase content ratio was less than 15%, so the impact resistance and durability were reduced. In Comparative Example 6, the raw material was processed without adding a surfactant, so the dispersibility of each raw material powder particle was reduced, the variation in the number of particles per unit area of the obtained sintered body was large, and the coefficient of variation in the number of crystal particles of 500 μm or more was greater than 0.2, and the thermal shock resistance and durability of the sintered body were reduced.
[0038] In Comparative Example 7, the mass ratio of mullite powder to coarse-grained alumina powder was greater than 1.30, so the amount of mullite crystal phase contained in the sintered body was large, the mullite phase content ratio exceeded 30%, and the stress effect generated by the thermal expansion difference between mullite crystals and corundum crystals was reduced, resulting in low thermal shock resistance and durability. In Comparative Example 8, sintering was performed at a sintering temperature lower than 1500°C, so sintering did not proceed, resulting in a sintered body with a porosity of more than 50% and an average pore diameter of more than 20 μm, which reduced the mechanical properties and resulted in low thermal shock resistance and durability. In Comparative Example 9, the mass ratio of coarse alumina powder to fine alumina powder was greater than 0.85, so that the amount of fine powder particles that bind the coarse powder particles together during firing was reduced, and the amount of coarse powder particles was increased, resulting in a large number of coarse crystal particles per unit area, with the number of crystal particles of 500 μm or more exceeding 15. The mechanical properties were reduced due to the reduced binding force, and the thermal shock resistance and durability were low. In Comparative Example 10, the impurities were greater than 1 mass % and firing was performed at a firing temperature higher than 1700° C., so that sintering proceeded too much, the porosity was lower than 30%, and as a result, the durability was low. In Comparative Example 11, the mullite powder / coarse alumina powder (mass ratio) was greater than 1.30 and the alumina content was lower than 90 mass%, resulting in a large amount of mullite crystal phase, the mullite phase content ratio exceeding 30%, and large distortion caused by the difference in thermal expansion between the mullite crystals and the corundum crystals, resulting in low thermal shock resistance and durability. [Industrial Applicability]
[0039] The lightweight alumina sintered body and the member for heat treatment of the present invention can be used as members for heat treatment, and can be used in general heat treatment such as containers, stands, and various firing furnaces for containing or placing objects to be heat treated. In particular, they can be suitably used for producing containers, setters, tubes, etc. used in the synthesis and firing of electronic materials and secondary battery materials, the firing of various ceramic products, metal melting, single crystal growth, etc.
Claims
1. A lightweight alumina sintered body that satisfies the following requirements (a) to (e): (a) The crystalline phase is composed of two phases, a corundum phase and a mullite phase, and the content of the mullite phase is 15 to 30%. (b) the alumina content is 90 to 94 mass %. (c) The porosity is 30 to 50%. (d) The average pore size is 20 μm or less. (e) Area 25mm 2 The number of crystal grains having a size of 500 μm or more present in the powder is 10 to 15, and the coefficient of variation in the number of crystal grains is 0.2 or less.
2. A heat treatment member comprising the lightweight alumina sintered body according to claim 1.
3. A coarse alumina powder having an alumina content of 99.7% by mass or more and an average particle size of 500 to 1400 μm is mixed with a fine alumina powder having an alumina content of 99.7% by mass or more and an average particle size of 5 to 20 μm so that the mass ratio of the coarse alumina powder to the fine alumina powder (coarse alumina powder / fine alumina powder) is 0.55 to 0.85, and the resulting mixture is added with a mass ratio of alumina to silica, i.e., Al 2 O 3 / SiO 2 The method for producing a lightweight alumina sintered body according to claim 1, comprising mixing and dispersing mullite powder having a mass ratio of 74 / 26 to 78 / 22 and an average particle size of 700 to 2000 μm with coarse alumina powder such that the mass ratio of the mullite powder to the coarse alumina powder (mullite powder / coarse alumina powder) is 0.85 to 1.30, forming the mixture, and firing the mixture at 1500 to 1700° C.
Citation Information
Patent Citations
Light-weight tool
JP1999189480A
Ceramic-burning tool and method for producing the same
JP2003252677A
Alumina refractory and method of producing the same
JP2011088759A